Human capital and lifetime income gains of scaling-up small-quantity lipid nutrient supplements among children under 2 years: A modelling analysis. - Nandita Perumal; Goodarz Danaei; Günther Fink; Mark Lambiris; Christopher R Sudfeld (PLOS Global Public Health)
Undernutrition in early childhood is associated with adverse health and developmental outcomes later in life and remains a persistent global public health problem. Providing small-quantity lipid nutrient supplements (SQ-LNS) to children aged 6-24 months improves child growth and neurodevelopmental outcomes, but the potential long-term benefits to human capital have not been previously estimated. We estimated the potential returns to schooling and lifetime income attributable to increasing coverage of SQ-LNS for children <2 years of age from 0% to 50% or 90% per five-year birth cohort in five countries (Bangladesh, Burkina Faso, Ethiopia, Pakistan, and Uganda) with a high burden of undernutrition. Random-effects meta-analyses were used to estimate the effect of SQ-LNS on child development using evidence from randomized controlled trials, and to estimate the returns to lifetime income as a function of change in development based on a de novo meta-analysis of observational economic studies. Gains in school years attributable to scaling-up SQ-LNS to 90% coverage ranged from 0.14 million school years (95% uncertainty interval [UI]: 0.064, 0.25) in Burkina Faso to 1.18 million school years (95%UI: 0.54, 2.11) in Pakistan per five-year birth cohort. With an effect size of 18% return in income per one standard deviation increase in development, the estimated gains in lifetime income ranged from $US 0.41 billion (95% UI: 0.20, 0.68) in Burkina Faso to $US 6.91 billion (95% UI: 3.32, 11.4) in Pakistan per five-year birth cohort. Returns in income per child were above the estimated per child cost of providing SQ-LNS. These findings demonstrate that scaling-up SQ-LNS among children aged 6-24 months may lead to substantial human capital gains in countries with a high-burden of child undernutrition. Longitudinal studies on the long-term effects of SQ-LNS are needed to refine model parameters and to better characterize the impacts on broader health and human capital outcomes.